2010
DOI: 10.1146/annurev.anthro.012809.105054
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Breeding and its Significance to the Demographic Success of Humans

Abstract: AN39CH25-Kramer ARI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
298
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(310 citation statements)
references
References 112 publications
5
298
1
6
Order By: Relevance
“…There is mounting evidence that menopause evolved via inclusive fitness benefits gained by helping kin; both postreproductive humans [11][12][13][14] and killer whales [15] increase the reproductive success and/or survival of their relatives. But how postreproductive females help their kin remains enigmatic.…”
Section: Resultsmentioning
confidence: 99%
“…There is mounting evidence that menopause evolved via inclusive fitness benefits gained by helping kin; both postreproductive humans [11][12][13][14] and killer whales [15] increase the reproductive success and/or survival of their relatives. But how postreproductive females help their kin remains enigmatic.…”
Section: Resultsmentioning
confidence: 99%
“…However, the large-scale datasets often used to demonstrate associations between kin availability and fitness outcomes are typically not suitable for testing whether such associations are driven by help from kin: usually an association between some measure of kin presence and a fitness outcome is all that is demonstrated (see exceptions : Waynforth 2012;Mathews and Sear 2013;Kaptijn et al 2010). There is a parallel literature, from anthropologists working in small-scale subsistence societies, which has clearly demonstrated that kin do provide alloparenting and other forms of help for one another (Gibson and Mace 2005;Hawkes, O'Connell, and Blurton Jones 1997;Ivey 2000;Kramer 2010;Meehan, Quinlan, and Malcom 2013). This supports the argument that kin help may be the cause of associations between kin and reproductive outcomes, but sufficiently detailed time−budget data are difficult to collect, so that it is rare to find datasets detailed enough to directly test whether kin help influences fitness outcomes.…”
Section: Introductionmentioning
confidence: 89%
“…In most human societies, mothers are not the sole caretakers of infants, and fathers, other relatives, and even unrelated individuals may participate in infant care (Geary 2005 ;Hewlett 1989 ;Hrdy 2008 ;Kramer 2010 ;Marlowe 2000 ) . Direct male care is facultative for our species and can range from being virtually absent to providing a substantial contribution to a child's upbringing.…”
Section: Catarrhinesmentioning
confidence: 99%